2012
DOI: 10.1116/1.3683057
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-enhanced and thermal atomic layer deposition of Al2O3 using dimethylaluminum isopropoxide, [Al(CH3)2(μ-OiPr)]2, as an alternative aluminum precursor

Abstract: The authors have been investigating the use of [Al(CH3)2(μ-OiPr)]2 (DMAI) as an alternative Al precursor to [Al(CH3)3] (TMA) for remote plasma-enhanced and thermal ALD over wide temperature ranges of 25–400 and 100–400 °C, respectively. The growth per cycle (GPC) obtained using in situ spectroscopic ellipsometry for plasma-enhanced ALD was 0.7–0.9 Å/cycle, generally lower than the >0.9 Å/cycle afforded by TMA. In contrast, the thermal process gave a higher GPC than TMA above 250 °C, but below this tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
53
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 94 publications
(81 reference statements)
12
53
0
Order By: Relevance
“…36 This trend is also reflected in the stoichiometry of the films which are slightly O rich at high temperatures. 6,7,21,32,37 At lower temperatures, the films become even more O rich, 6,7,21,32,36,37 in line with the AlO(OH) structure. The films prepared with thermal ALD are generally carbon free, even when deposited at low temperatures.…”
Section: Growth Mechanism Of Ald Of Al 2 Omentioning
confidence: 95%
See 2 more Smart Citations
“…36 This trend is also reflected in the stoichiometry of the films which are slightly O rich at high temperatures. 6,7,21,32,37 At lower temperatures, the films become even more O rich, 6,7,21,32,36,37 in line with the AlO(OH) structure. The films prepared with thermal ALD are generally carbon free, even when deposited at low temperatures.…”
Section: Growth Mechanism Of Ald Of Al 2 Omentioning
confidence: 95%
“…The deposition temperature has a significant influence on the ALD process. 6,13,[30][31][32] The lowest practical temperature for thermal Al 2 O 3 ALD is $150 C. At lower temperatures, the ALD cycle becomes quite long because H 2 O is difficult to remove at low temperatures resulting in extremely long purge steps. Also the mass density of the deposited Al 2 O 3 decreases significantly for deposition temperatures below 150 C. 6 For example, Groner et al showed that a deposition at 33 C requires a cycle time of $200 s (compared to, e.g., 4 s) and the mass density of the film is $20% less than for films grown at high temperatures.…”
Section: Growth Mechanism Of Ald Of Al 2 Omentioning
confidence: 99%
See 1 more Smart Citation
“…A saturated process was developed for plasma and thermal ALD in our OpAL reactor. 199 Slightly longer dosing times ($100 ms) were required for DMAI than for TMA, which can be A negative Q f of $4 Â 10 12 cm À2 was obtained. Wafers with a resistivity of $2 X cm (p-type) were used as substrates.…”
Section: Dmaimentioning
confidence: 99%
“…Dimethylaluminum isopropoxide (DMAI) was proposed by a few groups as an alternative CVD precursor to produce alumina films using evaporation or bubbling systems . DMAI was also tested for atomic layer deposition (ALD) of alumina in a few instances . This molecule consists of an Al atom linked to two methyl and one isopropyl groups, and has an intermediate structure between ATI and TMA.…”
Section: Introductionmentioning
confidence: 99%